Experiences and challenges of a redesign process with the support of an AI assistant on an educational platform - Borges, Jonathan Martins; Araújo, Rafael Dias (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2024: Anais do XXIII Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2024)
Artificial Intelligence (AI) has contributed to the advancement of many knowledge areas. In particular, Large Language Models (LLMs) has become a trending topic and its application has been studied in different contexts, including human-computer interaction (HCI) and interface design research. Interaction design (IxD) and interface design (UI) benefit from these technologies, in which some tasks can be automated with new tools for creating more efficient interfaces. This experience report explores the integration of AI in the redesign process of the educational platform Classroom eXperience (CX), utilizing models such as GPT-4 and Gemini 1.5. The study shows that AI can complement the work of designers, providing precise analyses and suggestions to improve usability and user experience, although human supervision remains essential to validate and implement these improvements.